Perceived Barriers of Utilization of Non- Pharmacological Pain Management among Post- Operative Patients (Nurse’s Perspectives) at Khartoum Public Hospitals, 2021-2022 (International Journal of Scientific Research and Management (IJSRM), 2022)
Background: Pain in surgical patients considered one of the most serious complaints in the postoperative period, and if not controlled, it can leads to many problems. There are still significant barriers limiting the capacity for effective pain management such as healthcare system-related, medical staff-related and patient-related.Aim: This study aimed to identify the perceived barriers in utilization of non- pharmacological pain management among post- operative patients (nurse’s perspectives). Methods: This was descriptive cross sectional hospital based study conducted at selected public hospitals in Khartoum State. It’s include (106) nurses working at general surgical words. Data was collected by a self-administered questionnaire and analysed by using computer statistical package of social program and presented in form of tables.Results: study revealed that, half of participants sometimes using non- pharmacological methods to manage post- operative pain. Rregarding nurse’s related barriers, participants reflect a high response with lack of experience in using non-pharmacological methods, inadequate time to deliver non-pharmacological pain relief measures, limited nurse-patient interaction and staff shortage.Conclusion: The top perceived barriers were related to post- operative pain management, nurses´ workload, unavailability of pain assessment and management protocols, lack of guideline regarding pain management and lack of resources such as equipments and materials. So, study recommends that, Obstacles encountered by nurses could be alleviated by adequate professional cooperation between physicians and nurses; with this goal in mind, meetings should be organized for the two professional groups to discuss pain management issues and analyze suggested procedures.